Creep stiffness and voids characteristic of asphalt mixture with waste cooking oil after aging - Putra Jaya, Ramadhansyah; Noram Irwan, Ramli; Lopa, Romana Sarker; Nordiana, Mashros; Norhidayah, Abdul Hassan; Haryati, Yaacob; Mohd Rosli, Hainin; Muhammad Naqiuddin, Mohd Warid; Mohd Khairul Idham, Mohd Satar (AIP Publishing, 2018)
The creep stiffness and voids properties of asphalt mixture with waste cooking oil at different aging conditions i.e. unaged, short term aging and long term aging were presented in this study. 60/70 penetration grade asphalt binder was used in this investigation. 5% of asphalt binder was replaced with untreated and treated waste cooking oil. The voids properties of asphalt mixture were determined based on Marshall Mix design test where creep stiffness were evaluate through dynamic creep test. In general, the results showed that creep stiffness modulus at the three different aging conditions were improved when treated waste cooking oil was used. However, the creep stiffness was decreased when untreated waste cooking oil was introduced in asphalt mixture.